Sa’id, Abdul-Jabbar. “Methodology of Approaching the Sunnah of the Prophet,” Year 5, Issue 18 (Fall 1420 AH/ 1999 CE), Pp. 53-88. - سعيد, عبد الجبار (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 1999)
Abdul-Jabbar Saʿid’s article explains the importance and objectives of how to approach the Sunnah and the previous efforts in it, addressing the subject matter’s terminology, how the Sunnah is an authentic source, and describing seven manifestations of error in approaching the Sunnah. It then sets guidelines for the following methodology: authentication of a ḥadith’s sanad (chain of transmittance) and its matn (text) according to specified conditions; referring it to the Qur’an and to the facts of universe, history, and science; referring it to the maqāṣid (objectives of Shariʿah); and understanding a hadith according to the time, place, and context in which it occurred and accurately projecting it on the current reality. It concludes with a call for continued efforts by the Ummah’s scholars to respond to the issues raised in this research.